(untitled) (Proceedings of Faculty of Civil Engineering, 2019)
Since the 19th century is the century of the development of structures, the 20th century is the century of the development of new construction and finishing works materials. Thus, the development and use of the structures introduced in the 19th and 20th centuries is also followed by the development of the façade systems. The paper analyzes the development of the case studies in Rijeka and its surrounding area.